Impaired Spatial Learning and Memory in Middle-Aged Mice with Kindling-Induced Spontaneous Recurrent Seizures - Liu, Haiyu; Stover, Kurt R.; Sivanenthiran, Nila; Chow, Jonathan; Cheng, Chloe; Liu, Yapeng; Lim, Stellar; Wu, Chiping; Weaver, Donald F.; Eubanks, James H.; Song, Hongmei; Zhang, Liang (Frontiers in Pharmacology, 2019)
Temporal lobe epilepsy (TLE) is the most common and often drug-resistant type of epilepsy in the adult and aging populations. Kindling through repeated brief stimulation of limbic structures is a commonly used model of TLE. Particularly, extended kindling can induce spontaneous recurrent seizures in several animal species. However, kindling studies in middle aged, aging, or aged animals remain scarce and currently little is known about kindling induced behavioral changes in middle-aged/aging animals. We therefore attempted to provide more information in this area using a mouse model of extended hippocampal kindling. We conducted experiments in middle aged mice to model new-onset epilepsy in adult/aging populations. Mice experienced twice daily hippocampal stimulations or handling manipulations for 60-70 days and then underwent continuous EEG-video monitoring to detect spontaneous recurrent seizures. Extended kindled mice consistently exhibited spontaneous recurrent seizures with mean incidences of 6-7 events per day, and these seizures featured EEG discharges and corresponding convulsions. The handling control mice showed neither seizure nor aberrant EEG activity. The two groups of mice underwent the Morris water maze test of spatial learning and memory 1-2 weeks after termination of the kindling stimulation or handling manipulation. During visible platform trials, the kindled mice took a longer distance and required more time than the control mice to find the platform. During hidden platform trials, the kindled mice showed no improvement over 5-day trials in finding the platform whereas the control mice improved significantly. During probe tests in which the hidden platform was removed, the kindled mice spent less time than the controls searching in the correct platform location. There were no significant differences between the kindled and control mice with respect to swim speed or total locomotor activity in an open field test. Together these observations indicate that the extended kindled mice with spontaneous recurrent seizures are impaired in spatial learning and memory as assessed by the Morris water maze test. We postulate that the extended hippocampal kindling in middle aged mice may help explore epileptogenic mechanisms and comorbidities potentially relevant to new-onset temporal lobe epilepsy in adult and aging patients.